Persepsi Mahasiswa Baru yang Mengalami Kesurupan Terkait Stres Akademik - Silalahi, Malianti; Casman, Casman; Kurniawan, Kurniawan; Khoirunnisa, Khoirunnisa (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2022)
Introduction: dissociative trance is susceptible to occur in first year student. This is associated with their ability in dealing with academic stress. Objective: this study aimed to explore the perception of freshmen year who experience trance that were associated with stress. Methods: this qualitative research used descriptive methods. The sampling technique was a purposive sampling. The participants were freshmen in the first semester and students who experienced mass trance. This study used in-depth interview as data collection technique. Result: there were five main themes, psychological responses and coping mechanisms of freshmen year who experience a trance in adapting to a new environment, perceptions of students who experience a trance that are in line with attitudes and emotional states in dealing with stress, impact namely of unresolved stressors on students who are in a trance experiencing a mass trance, the support system needed by students who are in a trance to cope with stress, and the process of the occurrence of a trance. Conclusion: stress factors and responses to cope the stress, as well as beliefs and heredity are considered as triggers for the occurrence of trance in freshmen year. This study described students' perceptions of the occurrence of trance. Further research is needed to find out the specific factors of trance.